Hubungan pelaksanaan discharge planning dengan motivasi keluarga dalam merawat pasien resiko jatuh - Rohmah, Eis Ainun; Kusumaningsih, Dewi; Gunawan, M.Ricko; Isnainy, Usastiawaty C.A.S. (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Discharge planning is a crucial process for patients at risk of falling. Patient safety is a primary concern in hospitals, given that falls can result in serious injury and prolong recovery time. Families play a crucial role in supporting patients during discharge, making family motivation in caring for patients a crucial factor. Purpose: To determine the relationship between discharge planning implementation and family motivation in caring for patients at risk of falling. Method: This quantitative study used an analytical survey design with a cross-sectional approach. The population in this study were respondents at risk of falling at Bintang Amin Hospital in March 2025. A total sampling technique was used for 72 patients. Data analysis used univariate and bivariate analyses using the chi-square test. Results: The majority of discharge planning implementation was categorized as poor (42 respondents (58.3%). The majority of motivation to care for patients at risk of falling was categorized as moderate (40 respondents (55.6%), with a chi-square test result of p-value = 0.013 < 0.05). Conclusion: There is a relationship between discharge planning implementation and family motivation in caring for patients at risk of falling.   Keywords: Discharge Planning; Fall Risk; Family Motivation.   Pendahuluan: Discharge planning merupakan proses penting dalam pasien dengan risiko jatuh. Keselamatan pasien menjadi perhatian utama di rumah sakit, mengingat insiden jatuh dapat mengakibatkan cedera serius dan memperpanjang waktu pemulihan. Keluarga memiliki peran krusial dalam mendukung pasien selama masa pemulangan, sehingga motivasi keluarga dalam merawat pasien menjadi faktor yang sangat penting. Tujuan: Untuk mengetahui hubungan pelaksanaan discharge planning dengan motivasi keluarga dalam merawat pasien resiko jatuh. Metode: Jenis penelitian kuantitatif menggunakan desain Survei Analitik dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah responden dengan resiko jatuh di RS Bintang Amin yaitu bulan Maret Tahun 2025 sebanyak terdapat 72 pasien menjadi sampel dengan menggunakan teknik total sampling. Analisa data menggunakan univariat dan bivariat menggunakan uji chi square. Hasil: Sebagian besar pelaksanaan discharge planning dengan kategori kurang baik sebanyak 42 responden (58.3%). Sebagian besar motivasi merawat pasien resiko jatuh dengan kategori sedang sebanyak 40 responden (55.6%) dengan hasil uji chi square dengan p-value = 0.013 < 0.05. Simpulan: Terdapat hubungan pelaksanaan discharge planning dengan motivasi keluarga dalam merawat pasien resiko jatuh.   Kata Kunci: Discharge Planning; Motivasi Keluarga; Resiko Jatuh.